Prediagnostic Blood Selenium Status and Mortality among Patients with Colorectal Cancer in Western European Populations - Jacqueline Roshelli Baker; Sushma Umesh; Mazda Jenab; Lutz Schomburg; Anne Tjønneland; Anja Olsen; Marie-Christine Boutron-Ruault; Joseph A. Rothwell; Gianluca Severi; Verena Katzke; Theron Johnson; Matthias B. Schulze; et al. (Biomedicines, 2021)
A higher selenium (Se) status has been shown to be associated with lower risk for colorectal cancer (CRC), but the importance of Se in survival after CRC diagnosis is not well studied. The associations of prediagnostic circulating Se status (as indicated by serum Se and selenoprotein P (SELENOP) measurements) with overall and CRC-specific mortality were estimated using multivariable Cox proportional hazards regression among 995 CRC cases (515 deaths, 396 from CRC) in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort. Se and SELENOP serum concentrations were measured on average 46 months before CRC diagnosis. Median follow-up time was 113 months. Participants with Se concentrations in the highest quintile (≥100 µg/L) had a multivariable-adjusted hazard ratio (HR) of 0.73 (95% CI: 0.52–1.02; Ptrend = 0.06) for CRC-specific mortality and 0.77 (95% CI: 0.57–1.03; Ptrend = 0.04) for overall mortality, compared with the lowest quintile (≤67.5 µg/L). Similarly, participants with SELENOP concentrations in the highest (≥5.07 mg/L) compared with the lowest quintile (≤3.53 mg/L) had HRs of 0.89 (95% CI: 0.64–1.24; Ptrend = 0.39) for CRC-specific mortality and 0.83 (95% CI: 0.62–1.11; Ptrend = 0.17) for overall mortality. Higher prediagnostic exposure to Se within an optimal concentration (100–150 µg/L) might be associated with improved survival among CRC patients, although our results were not statistically significant and additional studies are needed to confirm this potential association. Our findings may stimulate further research on selenium’s role in survival among CRC patients especially among those residing in geographic regions with suboptimal Se availability.